A Note on the Regularity of the Solutions to Two Variational Inequalities Involving a Pseudodifferential Operator - Randolph G. Cooper (International Journal of Mathematics and Mathematical Sciences)
The regularity of solutions to variational inequalities involving local operators has been studied extensively. Less attention has been paid to those involving nonlocal pseudodifferential operators. We present two regularity results for such problems.